Synthesis of Water-Soluble Iridium (III)-Containing Nanoparticles for Biological Applications - Huanzhi Hou; Pengfei Sun; Quli Fan; Xiaomei Lu; Cheng Xue; Yixue Zhang; Sichao Tian; Wei Huang (Journal of Chemistry)
Water-soluble nanoparticles (Ir/PGlc-NP, Ir/β-1,3-glucan-NP) based on water-soluble glycopolymers (PGlc), β-1,3-glucan polysaccharide, and conjugated phosphorescent Ir (III) complexes were successfully synthesized by self-assembly. The obtained nanoparticles have good spherical morphological characterization with a mean diameter of 50 nm measured by TEM. Ir/PGlc-NP and Ir/β-1,3-glucan-NP showed the same emission maxima at 565 nm in aqueous solution and both caused effective apoptosis and death of HepG2 and Hela cells after being irradiated at 445 nm for 30 min in vitro. Fluorescence cellular imaging was conducted by confocal laser scanning microscopy (CLSM) using HepG2 cells as the model cell in which the nanoparticles had successfully entered into the cytoplasm with high brightness. Furthermore, after injecting the nanoparticles into live mice in vivo, the real-time fluorescence imaging as well as the nanoparticles distribution in organs at 24 hours after administration indicated that these nanoparticles can serve as fluorescent imaging contrast for further biological applications.